Hubungan Kandungan Informasi Arus Kas, Komponen Arus Kas dan Laba Akuntansi dengan Harga atau Return Saham - Triyono Triyono; Jogiyanto Hartono (The Indonesian Journal of Accounting Research, 2013)
The Indonesian Institute of Accountants (IAI) published the Statement of Financial Accounting Standard (PSAK) No. 2, “Statement of Cash Flows” requires companies to publish the statement of cash flows beginning from January 1, 1995. The objective of the study is to examine the association of information content of total cash flows, components of cash flows, and accounting income with stock prices or stock returns. Another  objective of the study is to compare the predictive power of between of total cash flows and accounting income with their relation to stock prices or stock returns.As much as 54 manufacturing firms listed in the Jakarta Stock Exchange (BEJ) were taken as a sample using a purposive sampling method. Data from audited financial statements were taken from Indo-exchange files. The statistics method used to test hypotheses is a linear multiple regression. Two models were considered: levels and return models. The multicollinearity test shows that there is no association between independent variables in the regression models, indicating multicollinearity is a serious problem. The heteroscedasticity test shows that variances of disturbances are constant for all observation in independent variables. Therefore, heteroscedasticity is not a problem. Results from diagnostic tests suggest that regression models used in this study are unbiased.The empirical results indicate that disaggregation of total cash flows into their components as required by PSAK No.2 are significantly associated with stock prices in the levels model. This means that the accounting authority has correctly mandated the publication statement of cash flows. In contrast, the results of the study indicate that total cash flows, components of cash flows, and accounting income are not associated with stock returns in the return model.